Psoriatic spondylitis in a patient with classical rheumatoid arthritis. Issue 691 (May 1983) - Thurtle, O. A.; Dumbelton, I. B.; Preston, J. R.; Cook, P. L.; Cawley, M. I.
Abstract : A patient exhibiting typical features of classical rheumatoid arthritis and psoriatic spondylitis is described. The patient, a woman, presented at the age of 29 with an inflammatory arthritis. Twenty years later, she developed psoriasis, and after a further 3 years, she was first noted to have rheumatoid nodules and to be strongly seropositive. Now at the age of 60, she has a rigid spine with radiographic changes of spondylitis. Neither rheumatoid arthritis, nor psoriatic spondylitis can account for all the features of her disease and there is evidence to suggest that both conditions combined to damage her peripheral joints.